Biosecurity for highly pathogenic avian influenza : issues and options. (Rome FAO, 2008)
This paper describes in detail the current situation and state of knowledge about biosecurity in relation to H5N1 HPAI, discusses species- and sector-specific issues, proposes possible options for biosecurity in important parts of the domestic poultry and captive bird sector, stresses the importance of situating biosecurity in appropriate economic and culture settings, and makes the case for the role of communication.--Publisher's description.
Keywords: Avian influenza; Avian influenza -- Prevention